Penilaian praktikum mahasiswa Poltekkes Kemenkes Yogyakarta berbasis web - Mohamad Mirza Fauzie; Dina Fadhilah (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
Industrial revolution 4.0 or called the digital era which means all aspects of our lives are related to digital devices. Using web-based software can reduce data management problems, both in terms of data storage and data sharing with other users who need data, it also provides fast, precise and accurate data and information that is needed. Sooner or later the education system must evolve following the development of this digital era. For this we need a system for our educations. Make an application for assesing student- practices with web based that can make it easier for students to submit practicum reports, facilitates lecturers in assessing practicum activities and student practices reports. This research is a quantitative study with design research and development study (R and D). first by making an application which was then tested by Lecturers, Instructors, Students at the Polytechnic of the Ministry of Health Yogyakarta. Then the application is approved by Information Technology Experts and users namely Lecturers, Instructors and Students. Quantitative data is created in the feasibility presentation, whether the information system is created is appropriate or not.